An Inhospitable Cryptand: The Importance of Conformational Freedom in Host‐Guest Complexation. Issue 21 (21st March 2019) - Gibson, Harry W.; Huang, Feihe; Zhao, Run; Shao, Li; Zakharov, Lev N.; Slebodnick, Carla; Rheingold, Arnold L.
Abstract : Two new cryptands were synthesized from bis(5‐bromomethyl‐1, 3‐phenylene)‐32‐crown‐10 (4 ). The third arms, containing 19 or 21 atoms, were installed via Williamson ether syntheses with bisphenols containing 2, 6‐disubstituted pyridines. 2, 6‐Diaminopyridine was converted into the bis( p‐ hydroxybenzoyl) derivative 3 for the first cryptand (5 ) and 2, 6‐dicarboxypyridine was converted into the bis( p‐ hydroxybenzylamide) 9 for the second cryptand (10 ). Cryptand 5 did not complex viologen derivatives 11 –13 to an extent detectable by 1 H NMR. We attribute the lack of complexation between viologen derivatives and 5 to its lack of conformational flexibility that prevents π‐stacking, a necessary component for complexation of viologens. In contrast longer and more flexible cryptand 10 did complex dimethyl paraquat (11 ) with K a = 1.6 (±0.2) × 10 3 m –1 in acetone at 23 °C, probably by π‐stacking with the p ‐oxybenzyl moieties of the host, made available by its enhanced flexibility. Abstract : A conformationally rigid pyridyl cryptand does not bind viologens! The rigidity of the third arm of this cryptand causes the 1, 3, 5‐phenylene rings (shown in pink) of the host to be nearly orthogonal and too far apart to π‐stack with viologen guests. An analogous cryptand with a slightly longer and more flexible third arm does complex dimethyl paraquat.